ORDNUNGSPOLITIK UND GEORDNETE EUROPÄISCHE INTEGRATION - BOKAJŁO, Justyna (Studia Universitatis Babes-Bolyai Studia Europaea, 2019)
Regulatory Policy and Orderly European Integration. This paper investigates the role of USA in promoting of economic order (Ordoliberalism) in Germany after the second world war and further its impact on the bottom-up process of Europeanization. Moreover, the United States of America as a modern federation has become an inspiration for European federation concepts. The main hypothesis is contained in the statement that the depart from the policy of order by the USA has been disastrous for international order. The consequence of this was financial and economic crisis, which further deepened the EU and EMU disorder.